Ultra-high thermal stability of sputtering reconstructed Cu-based catalysts - Yu, Jiafeng; Sun, Xingtao; Tong, Xin; Zhang, Jixin; Li, Jie; Li, Shiyan; Liu, Yuefeng; Tsubaki, Noritatsu; Abe, Takayuki; Sun, Jian (Nature communications, 2021)
The rational design of high-temperature endurable Cu-based catalysts is a long-sought goal since they are suffering from significant sintering. Establishing a barrier on the metal surface by the classical strong metal-support interaction (SMSI) is supposed to be an efficient way for immobilizing nanoparticles. However, Cu particles were regarded as impossible to form classical SMSI before irreversible sintering. Herein, we fabricate the SMSI between sputtering reconstructed Cu and flame-made LaTiO 2 support at a mild reduction temperature, exhibiting an ultra-stable performance for more than 500 h at 600 °C. The sintering of Cu nanoparticles is effectively suppressed even at as high as 800 °C. The critical factors to success are reconstructing the electronic structure of Cu atoms in parallel with enhancing the support reducibility, which makes them adjustable by sputtering power or decorated supports. This strategy will extremely broaden the applications of Cu-based catalysts at more severe conditions and shed light on establishing SMSI on other metals. Applications of Cu catalysts at high-temperature is a long-sought goal but limited by their serious deactivation due to low copper’s Tammann temperature. Here, the authors introduce an encapsulation layer to improve thermal stability at 800 °C by reconstructing electronic structure of Cu atoms.